Influence of repeated intravital extraction of eggs from sturgeon hybrids on their oogenesis under conditions of recirculation aquaculture system - Olga P. Filippova; Svetlana V. Piyanova; Sergey E. Zuevsky (Известия ТИНРО)
Dynamics of cytomorphological characteristics of oocytes in ovaries is considered for two sturgeon hybrids: besters of the breed Burtlevskaya Huso huso (Linnaeus) x Acipenser ruthenus (Linnaeus) and the breed Aksayskaya Acipenser ruthenus x ( Huso huso x Acipenser ruthenus ) on the experimental data obtained under controlled conditions in the aquatic complex in Moscow (Russia) in 2010-2012. Methods of intravital eggs extraction, ultrasound diagnostics, biopsy with the probe, anesthesia and histological analysis are applied. Structure of membrane is similar for straight sturgeon species and hybrids, but the membrane thickness and the term of its emergence on certain maturity stage are somewhat different, so the eggs of bester could be distinguished by the oocyte membrane thickness. Mean interspawning interval for the hybrids in conditions of recirculation aquaculture system at water temperature 20-21 °C is determined as 10-12 months.